PERILAKU MAKAN MONYET EKOR PANJANG (Macaca fascicularis) - , RYAN ADI SATRIA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Long-tailed Macaque (Macaca fascicularis Raffles, 1821) is the most successive primate and widely distributed throughout Southeast Asia, but still inadequately knowledged on its ecology as well as biology, particularly for the wild population. Most of studies are focusing on the macaques that live in disturbed habitats. The presence of macaques as a component of the ecosystem becomes very important in limited habitats such as tropical dry forest ecosystem of Rinca Island. This research aimed to (1) identify the troop size and composition of long-tailed macaque, (2) to identify the diet diversity of long-tailed macaque, and (3) to identify the time budget and spatial use on feeding behavior of longtailed macaque in tropical dry forest ecosystem of Rinca Island. Six days observation with concentration count method around macaque's sleeping site was conducted to estimate the troop size and composition. The diet data collection was carried out by frequency method. The diet type diversity was analyzed with Shannon-Wiener Diversity Index. Focal animal one-zero time sampling method was used to observe the macaque feeding behavior. Time duration and position of each behavior unit was recorded to identify the time budget and spatial use on feeding behavior of M. fascicularis. The results showed that M. fascicularis in tropical dry forest of Rinca Island has large troop size which is 40 individuals/troop. The macaque's troop composition consist of 11 individuals of adult male, 13 individuals of adult female, 12 individuals of juvenile, and 4 individuals of infant. ID Shannon- Wiener of vegetative food is 2.12 and ID Shannon-Wiener of total food is 2.23. The feeding behavior time budget of adult female, adult male, and juvenile are 32.58%